Pengaruh Kepemilikan Manajerial dan Pengungkapan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan pada Perusahaan Property dan Real Estate di Bursa Efek Indonesia 2019–2023 - Lidya Martha; Nurul Izati; Aminar Sutra Dewi; Riri Mayliza; Ratnawati Raflis (ARZUSIN, 2026)
Firm value has become a central concern in the finance literature because it reflects the market’s perception of a company’s long-term prospects and performance; however, studies that specifically examine the effects of managerial ownership and Corporate Social Responsibility (CSR) disclosure in the property and real estate sector in Indonesia remain relatively limited. This study aims to analyze the effect of managerial ownership and CSR disclosure on firm value in Indonesian property and real estate sector companies. A quantitative approach with a causal research design was employed, involving 23 companies selected using purposive sampling for the 2019–2023 period. Data were obtained from annual reports and analyzed using panel data regression with the aid of EViews 12 software. The results show that managerial ownership does not have a significant effect on firm value, whereas CSR disclosure has a positive and significant effect on firm value. These findings support legitimacy theory and enrich the corporate governance literature in the context of the property and real estate sector in Indonesia. The study concludes that CSR disclosure is an important strategy for enhancing firm value, with theoretical implications for the development of finance and governance literature and practical implications for management in formulating sustainability policies oriented toward increasing firm value.